A new analytical solution based on joint relaxation for analyzing symmetrical block stability. (20th November 2011) - Bagheri, M.; Stille, H.
SUMMARY The magnitude of clamping forces has a significant influence on the estimated ultimate pullout force of a block. The Crawford–Bray equation, which is fundamental in considering clamping forces, is only a function of horizontal stress and block height. Further research to incorporate the influence of induced stress in block stability analysis was considered, but all the previous analytical solutions for analyzing block stability assume a continuum medium to estimate clamping forces and do not allow joint deformations to occur before block movement due to gravity. Assuming a continuous medium to estimate clamping forces leads to an overestimation of block stability and therefore unsafe design. In this paper, an attempt has been made to deepen the understanding of the block failure mechanism and correct the estimated magnitude of clamping forces in a discontinuous medium. A conceptual model is proposed based on the loading–unloading of the block from an in‐situ state to failure. Based on this model, an analytical solution has been developed that calculates clamping forces in a discontinuous medium. The validity and model uncertainty of the solution were checked for different conditions. The new analytical solution is both precise and accurate and can be used as a design tool to estimate block stability. Copyright © 2011 John Wiley & Sons, Ltd.